Temperature Variation in Breast Tissue Model With and Without Tumor Based on Porous Media - Shrestha, Sharmila; K.C., Gokul; Gurung, Dil Bahadur (Journal of Nepal Mathematical Society, 2021)
The human body is made by 200 different types of cells, which are separated by voids. Blood supplies the nutrients and minerals to all cells within the tissue through these voids. The breast tissue is treated as a porous media in the study. Tumor includes the vascular (blood) and the extra-vascular (solid) regions. The porosity of a tumor is higher than normal tissue. The present work deals with the temperature variation of normal and tumorous breast tissue based on porous media. The finite element method is used to solve the two-dimensional bio-heat equation. The results show that the temperature profile of normal breast tissue in the porous media model is almost identical with the conventional bio-heat model at correction factor is equal to 0:6. The temperature of tumor region in the porous media model is slightly lower than the conventional bio-heat model. When the porosity is increased, the temperature of normal breast tissue is increased. But in tumorous breast tissue, the temperature is slightly increased in skin surface to anterior part of the tumor and slightly decreased in tumor region. The temperature of normal and tumorous breast tissue is increased when metabolism, blood velocity, and room temperature are increased in the porous media model. The central temperature of the tumor region reaches a steady state faster than anterior and posterior temperature of both normal and tumorous breast tissue in conventional bio-heat model and porous media model.